(untitled) (International Journal of Physiotherapy, 2016)
Background: Shoulder pain is the second most common musculoskeletal disorder treated by physical therapists. The cause for the shoulder pain is multifactorial. However, a specific diagnosis is crucial in the right management of shoulder dysfunction. Therefore, the aim of this study was to find out the efficacy of integrating the MRI for the accurate diagnosis and impact of this on rendering the effective physical therapy interventions in shoulder dysfunction patients. Methods: A retrospective study conducted on 14 patients who undergone an MRI with a 1.5 T unit MAGNETOM Symphony (Siemens), for their shoulder pain, where the diagnosis might be Muscle tears like, subscapularis, infraspinatus,supraspinatus and teres minor muscles; subacromial or subdeltoid bursitis and labral tears were included. All the subjects were then continued with usual physical therapy treatments for four weeks depending on their diagnosis which includes; advice, stretching, mobilization and strengthening exercises, manual therapy, massage, strapping, and electrotherapy . The outcome measures documented from the case sheet were; Visual Analogue Scale grade and passive range of motion of shoulder external / internal rotation and abduction. Results: Paired t test was used to compare the PROM between pre rehabilitation and post rehabilitation testing and the non parametric test, Mann Whitney U test was used for the comparison of VAS. All patients showed a significant improvement in VAS and PROM of abduction, internal and external rotation following physical therapy (P≤ 0.05). Conclusion: MRI is found to be a reliable method of diagnostic procedure for the shoulder pain and the integration of MRI and physical therapy to treat shoulder dysfunction leads to a better outcome.